2016
DOI: 10.1039/c6ra06634h
|View full text |Cite
|
Sign up to set email alerts
|

A new strategy for hydrogen storage using BNNS: simultaneous effects of doping and charge modulation

Abstract: The adsorption behavior of hydrogen molecule (H2) on neutral and charged states of C-, Si- and P-doped boron nitride nanosheets (BNNSs), is investigated using density functional theory (DFT) method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…By using pseudopotential DFT, Jhi and Kwon found that the binding energy of H 2 for moderately substituted BN nanotubes is increased by as much as 50 % on top of carbon that substitutes boron (i.e., −8.7 vs. −13 kJ mol −1 ) . Such a potential was computationally supported in a few other works, but the prediction has not been confirmed by experimental results yet . Instead, one may cite the work reported by Portehault et al.…”
Section: Avenues For Improvementsmentioning
confidence: 98%
See 1 more Smart Citation
“…By using pseudopotential DFT, Jhi and Kwon found that the binding energy of H 2 for moderately substituted BN nanotubes is increased by as much as 50 % on top of carbon that substitutes boron (i.e., −8.7 vs. −13 kJ mol −1 ) . Such a potential was computationally supported in a few other works, but the prediction has not been confirmed by experimental results yet . Instead, one may cite the work reported by Portehault et al.…”
Section: Avenues For Improvementsmentioning
confidence: 98%
“…[36] Such ap otential was computationally supported in af ew other works, but the prediction hasn ot been confirmed by experimental resultsy et. [54][55][56][57][58] Instead, one may cite the work reported by Portehaulte tal. where nano-/mesoporousb oron carbon nitrides (e.g.,B 0.36 C 0.12 N 0.32 O 0.11 H 0.09 with a specific surface area of 1560 m 2 g À1 ,amicroporous volume of 0.64 cm 3 g À1 ,a nd am esoporousv olume of 2.23 cm 3 g À1 )r eversibly stored 1.07 wt %H 2 at À196 8Ca nd 1bar.…”
Section: Substitutional Doping Of Bnmentioning
confidence: 99%
“…Nanotubes have been extensively studied as potential adsorbents in sensing nanomaterials. Lin et al [26] made a comprehensive study on the effect of transition metal decoration on boron nitride nanotubes, whereas elements, such as aluminium, gallium and germanium have been widely used as a spread on nanotubes overall [27][28][29][30]. Other studies have shown that even the introduction of non-metal atoms, such as oxygen, can activate the overall surface of nanomaterials [31].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, compared to pure nanomaterials, it can be said that decorated nanomaterials have a higher efficiency [23]. Aluminum and gallium and germanium are the elements that have been widely used to activate the surface of nanosheets in theoretical studies [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%